Quantification of microcirculatory parameters by joint analysis of flow‐compensated and non‐flow‐compensated intravoxel incoherent motion (IVIM) data. (8th March 2016) - Ahlgren, André; Knutsson, Linda; Wirestam, Ronnie; Nilsson, Markus; Ståhlberg, Freddy; Topgaard, Daniel; Lasič, Samo
Abstract : The aim of this study was to improve the accuracy and precision of perfusion fraction and blood velocity dispersion estimates in intravoxel incoherent motion (IVIM) imaging, using joint analysis of flow‐compensated and non‐flow‐compensated motion‐encoded MRI data. A double diffusion encoding sequence capable of switching between flow‐compensated and non‐flow‐compensated encoding modes was implemented. In vivo brain data were collected in eight healthy volunteers and processed using the joint analysis. Simulations were used to compare the performance of the proposed analysis method with conventional IVIM analysis. With flow compensation, strong rephasing was observed for the in vivo data, approximately cancelling the IVIM effect. The joint analysis yielded physiologically reasonable perfusion fraction maps. Estimated perfusion fractions were 2.43 ± 0.81% in gray matter, 1.81 ± 0.90% in deep gray matter, and 1.64 ± 0.72% in white matter (mean ± SD, n  = 8). Simulations showed improved accuracy and precision when using joint analysis of flow‐compensated and non‐flow‐compensated data, compared with conventional IVIM analysis. Double diffusion encoding with flow compensation was feasible for in vivo imaging of the perfusion fraction in the brain. The strong rephasing implied that blood flowing through the cerebral microvascular system was closer to the ballistic limit than the diffusive limit. © 2016 The Authors NMR in Biomedicine published by John Wiley & Sons Ltd. Abstract : A joint analysis of flow‐compensated and non‐flow‐compensated data acquired with multiple diffusion encoding strengths was suggested for improved stability of IVIM analysis. In vivo measurements yielded reasonable microcirculatory parameter maps, and showed a strong rephasing effect in the flow‐compensated data, indicating that the limit of straight flowing blood is plausible for cerebral blood flow. Simulations showed that, in the ballistic limit, the joint analysis yields superior accuracy and precision compared with conventional IVIM analysis.